Redes sociales e instituciones comerciales en el imperio español, siglos XVII a XIX. México, Instituto Mora, UNAM, 342 pp. (2009)
Redes sociales e instituciones comerciales en el imperio español, siglos XVII a XIX. México, Instituto Mora, UNAM, 342 pp.